Behind the scenes: a cross-country study into third-party website referencing and the online advertising ecosystem - Nurse, Jason R. C.; Buckley, O. (Springer, 2017)
The ubiquitous nature of the Internet provides an ideal platform for human communication, trade, information sharing and learning. Websites play a central role in these activities as they often act as a key point of interaction for individuals in navigating through cyberspace. In this article, we look beyond the visual interface of websites to consider exactly what occurs when a webpage is visited. In particular, we focus on the various web scripts that are often programmatically executed, to explore the extent to which third-party sites are referenced. Our aim is to study these references and the ecosystem that they create. To gain maximal impact while also allowing for a cross-country comparison, our study is scoped to an assessment of the top 250 sites in the UK, USA, Germany, Russia and Japan. From our analysis, there are various novel contributions of note. These include the empirical identifcation of a vast ecosystem of third-party information processing sites, especially advertisement networks, and the evidential discovery of a few signifcant players irrespective of country and locale. Through a user study, we also fnd that while individuals do have some knowledge of the prevalence of advertisements in websites, their understanding of the variety of activities that occur upon visiting websites, is not widely known. Going forward, we therefore advocate for increased transparency in such activities and the wider online advertisement ecosystem.